Anomalously robust valley polarization and valley coherence in bilayer WS(2) - Zhu, Bairen (National Academy of Sciences, 2014)
We report the observation of anomalously robust valley polarization and valley coherence in bilayer WS(2). The polarization of the photoluminescence from bilayer WS(2) follows that of the excitation source with both circular and linear polarization, and remains even at room temperature. The near-unity circular polarization of the luminescence reveals the coupling of spin, layer, and valley degree of freedom in bilayer system, and the linearly polarized photoluminescence manifests quantum coherence between the two inequivalent band extrema in momentum space, namely, the valley quantum coherence in atomically thin bilayer WS(2). This observation provides insight into quantum manipulation in atomically thin semiconductors.